Giant recurrent aneurysmal bone cyst of the mandible - Banu, Khurshida (Medknow Publications & Media Pvt Ltd, 2012)
The Aneurysmal bone cyst (ABC) is an infrequent but well defined lesion occurring most commonly in the long bones, the pelvis and vertebrae. Only 1-2% of the lesions are known to occur in the maxillofacial region. Clinically, the lesion usually occurs in young adults below 20 years of age. Though there does not seem to be any marked gender predilection and slight preponderance towards females has been reported. Here we present a case of giant recurrent aneurysmal bone cyst in a 19 year old male patient treated by segmental resection and reconstruction with vascularized fibular graft.